Preparation, Identification, thermal and Spectroscopic Study of Schiff Bases Derived from Terephthalaldehyde and Their Binuclear Complexes with Some Transition Metals and Lanthanides - Hassan. M. A. Al-Redha (Journal of Global Pharma Technology, 2018)
AbstractThe study include preparation and Characterization and Thermal Analysis of four new compounds of the Schiff bases , This ligand was prepared in two steps, in the first step includes reacted terephthaldehyde with(1,2-ethylenediamine and 1,4-Diaminobutane) to give precursore compound which reacted in the second step with (O-Vanillin and 2-Hydroxy-1- naphthaldehyde ) to give the following ligands L1 = 6,6,-((1E,1,E)((((1,4Phenylenebis(methanylylidene))bis(azanylylidene))bis(ethane2,1diyl))bis(azanylylidenebis(methanylylidene) bis(2- methoxyphenol) L2 = 1,1,-((1E)-((((1,4-phenylenebis(methanylylidene)) bis(azanylylidene))bis(ethane 2,1- diyl))bis(azanylylidene))bis (methanylylidene)bis(naphthalene-2-ol) L3 = 6,6,-((1E,1,E)-((((1,4-Phenylenebis(methanylylidene)) bis(azanylylidene))bis(butan 4,1- diyl))bis(azanylylidenebis (methanylylidene) bis (2-methoxyphenol) L4 = 1,1,-((1E)-((((1,4-phenylenebis(methanylylidene)) bis(azanylylidene))bis((butan 4,1- diyl))bis(azanylylidene))bis (methanylylidene)bis(naphthalene-2-ol) The Binuclear complexes were synthesized by direct reaction of the corresponding metal chloride(CuCL2.2H2O,NiCL2.6H2O,SmCL3.6H2OCeCL3.6H2O ) with the ligands. The ligands and their complexes were characterized by using Elemental Analysis (C.H.N), Infrared Spectroscopy (FT-IR), (UV-Vis), X-Ray, Nuclear Magnetic Resonance Spectroscopy (1H-NMR) Mass Spectra, Magnetic sensitivity and Molar conductivity techniques were applied. The stoichiometry for ion metal and ligands of complexes has been studied in Continuous Variation method (Job method). for all complexes and with ratio (2:1), thermal analysis. The data of these measurements be done suggest configuration geometry to this Complexes